MANAJEMEN STRESS CALON LEGISLATIF PASCA PEMILIHAN UMUM LEGISLATIF TAHUN 2014 (Studi Kasus Pada Calon Legislatif Gagal) - Yuni Indah (Professional: Jurnal Komunikasi dan Administrasi Publik, 2016)
This study aimed to analyze the sources of stress, resilience indicators of individual candidates in facing stress, the level of stress and techniques to manage stress when candidates failed to gain political stance. The results showed that the source of stress was the political funds issued exceed the financial capacity of the contestants. Source of political funds obtained from the loan was not able to increase their electability because in addition to economic investment, political and social investment was also required. During the post-electoral, contestants who failed underwent stress of mild category to severe stress category. For mild stress contestants only perform a cooling-off was accompanied by a family. While for contestants who were severely depressed, they should be treated in a mental hospital. From the results of this study, it’s recommended the need for the role of political parties in dealing with contestants’ stress. The Government must be present in the stress of candidate problems in terms of policy, namely the duty of political parties and governments to facilitate recovery and mental health. Before the fight, the political parties should provide psychological education for mental preparedness to face the worst.